Formation and Breakdown of an Offshore Summer Cold-Water Zone and Its Effect on Phytoplankton - Li, Weiqi; Zhou, Xiangqian; Ge, Jianzhong; Ding, Pingxing; Liu, Dongyan (Frontiers in Marine Science, 2022)
Estuarine plume frontal zones typically form a vertical two-layer structure with low-salinity and a high-temperature plume during the summertime. However, two field surveys in the Changjiang River Estuary and its adjacent shelf waters identified a significant surface cold-water zone (CWZ) formation in the summers of 2014 and 2015. The sea surface temperature of the CWZ was 4°C lower than the multi-year summer average. Satellite images showed that the CWZ mainly appeared in the Yangtze Shoal during the periods of July 1–17, 2014, and July 3–19, 2015. A three-dimensional physical-biogeochemical coupled model was used to explore the formation mechanism of the CWZ. Our investigation revealed that an uncharacteristic northerly wind during the southerly monsoon resulted in a significant onshore retreat of the plume front. Vertical tidal mixing is stronger than the decreased stratification in the former plume-covered region, which resulted in the formation of the CWZ. This process was accompanied by relatively lower net heat flux, which also promoted CWZ formation. The formation of CWZ had a strong ecological impact; enhanced vertical mixing transported nutrients from the lower layer to the surface column, relaxing the CWZ’s phosphate limitation. CWZ formation also increased the depth of the mixed layer and turbidity level in the water column, forming a temporary light limitation in the center. At the margin of the CWZ, it formed a patch with a high concentration of chlorophyll a. The underwater light was sufficient once the plume was restored and the CWZ was stratified again, and the phytoplankton grew rapidly in the center of the CWZ.